Integrated Business Service Center Building with Neo-Vernacular Concept in Wajo Regency - Rahmatullah; Hasniar Baharuddin; Sultan La Obo (Universitas Ichsan Sidenreng Rappang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the economy of Wajo Regency. However, their development still faces fundamental obstacles such as limited market access, low management literacy, and the absence of adequate supporting facilities. Therefore, the construction of an appropriate Integrated Business Service Center (PLUT) Building is required, which is also capable of preserving local cultural heritage amidst the current of globalization. This study uses a descriptive qualitative approach to analyze site conditions, regulations, spatial flow, and the programmatic needs of PLUT services. The design foundation utilizes the concept of Neo-Vernacular Architecture through the reinterpretation of physical characteristics and philosophical values of traditional Bugis-Wajo architecture-such as stilt house typology, teddong roof shapes, and spatial organization-applied into a contemporary public facility design that is responsive to the tropical climate. The design results show that the integration of business service functions (consultation, training, business incubation, and product exhibition) can be effectively organized through adaptive spatial zoning that separates public and private areas. The building's visual design transforms traditional Bugis elements into a modern facade using hybrid materials (concrete, glass, laser-cut metal) and shading vegetation that optimizes natural ventilation and lighting. The Neo-Vernacular Architecture approach applied to the Wajo Regency PLUT Building successfully fulfills functional needs and preserves local identity. This facility succeeds in realizing sustainable public architecture that strengthens the MSME ecosystem while serving as a symbol for the local community.